Kajian Perspektif Ekonomi Hijau dalam Usaha Mikro: Tinjauan Strategi Pemberdayaan Perempuan Menuju Kemandirian Ekonomi Daerah Afirmasi Kabupaten Tolitoli - Ilham, Ilham; Irvan, Muhammad; Ismail, Ismail (FEB Universitas Mulawarman, 2025)
This study aims to examine the perspective of green economy in the development of micro enterprises in Tolitolo Regency, with a focus on women's empowerment strategies towards economic independence in the affirmation area. Through a qualitative and quantitative approach, this study analyzed 105 units of Micro, Small, and Medium Enterprises (MSMEs) spread across several sub-districts. The data obtained: 36 MSME units are managed by women, 11 units are managed by men and the remaining 58 units are inactive (no operational activities). The results of the study show that the majority of MSME business actors in the Tolitoli green open space are women, who play a strategic role in supporting the family and community economy. It was found that the application of green economy principles, such as the use of eco-friendly materials and sustainable production practices, is still limited but shows potential for growth. Women's empowerment strategies, such as green skills training, access to green capital, and institutional support, have been shown to contribute positively to increasing business capacity and strengthening local economic independence. This research recommends the need for synergy between local governments, financial institutions, and civil society organizations in creating an inclusive and sustainable green economic ecosystem, by making women the main actors of socio-economic transformation in the field of affirmation